TEACHERS’ PERCEIVED INFLUENCE OF HOME-GROWN SUPPLEMENTARY FEEDING PROGRAM ON READINESS OF PRIMARY SCHOOL PUPILS’ IN OSUN STATE - Ologele, Ibrahim; A. M., Abdulraheem; K.A., Jidda; Q.O., Abdulrasaq; Olayemi, Agunloye (The University of Kuningan, 2023)
ABSTRACTHome grown supplementary feeding program connotes a feeding plan designed to provide balanced diet meal for school children daily who are attending public primary school within a community. The provision of adequate nutrition aims at promotion of good health recognized as constituting the foundation of proper growth of the primary school children. This study investigated teachers’ perceived influence of home-grown supplementary feeding program on readiness of primary school pupils’ in Osun State. The objectives of the study were to: (i) examine if teachers perceived home-grown supplementary school feeding programme as influencing pupils’ enrolment and (ii) pupils comportment in Osun State. The descriptive research design of survey type was adopted for the study. The population of this study consists of the head teachers and teachers in Osun State. Multi-stage sampling techniques consisting of purposive, proportionate and simple random sampling techniques was used to select a sample size of 454 respondents. A researcher-designed validated questionnaire was used for data collection. A reliability coefficient (r) of 0.78 was obtained through split-half method. Data collection was conducted by researcher and research assistants. Inferential statistic of Ch-square (x2) was used to analyzed the formulated null hypotheses at 0.05 alpha level using Statistical Package for Social Science (SPSS) version 23.0. The findings of the study were that: teachers significantly perceived home-grown supplementary school feeding programme as influencing pupil’s enrolment in Osun State. (cal. x2 value = 794.90 > crit. x2 value = 16.92, df = 9 @ = 0.05) and ; teachers significantly perceived home-grown supplementary school feeding programme as influencing pupils’ comportment in Osun State. (cal. x2 value = 256.89 > crit. x2 value = 16.92, df = 9 @ = 0.05). The study concluded that teachers perceived home-grown supplementary feeding programe to promote pupils enrolment and class composure in Osun State. The researcher recommended that free varieties of food should be provided for pupil’s in school to encourage more enrolment and improve the attention span of the pupils in school.Keywords: teachers; perceived-influence; home-grown; readiness; pupils